La coprésence des touristes et des habitants au cœur de la résilience du tourisme urbain. Une analyse du marché de Noël des Champs Elysées à partir de données d’enquêtes et des téléphones mobiles - Marie Delaplace; Emmanuelle Gautherat; Leila Kebir (Études Caribéennes)
The co-presence of tourists and inhabitants in tourism destinations can generate conflicts and/or complementarity. The objective of this article is to question the effects of this co-presence through the lens of urban tourism resilience in the particular case of urban events. We intend to analyse if the co-presence of different types of tourists and inhabitants during such event is a factor of resilience. The analysis is illustrated by a survey conducted on the Champs Elysees Christmas market from December 7, 2015, to January 10, 2016, just after the attacks of November 2015. These data are put in perspective with the mobile data (flux vision Orange) on Christmas market attendance in 2016. If the resilience of the destination seems to exist in volume, the structure of attendance is nevertheless impacted. The sensitivity of tourists to terrorist attacks varies according to their origin. Moreover, the presence of residents but also of some French tourists on this market, during the period following the attack, helped to absorb a part of the shock due to the sharp decrease in international tourist arrivals, until these arrivals recover. However, the uses and practices of the market by residents and tourists are partly different, thus questioning the ability of the suppliers to adapt.